Genotype x environment interactions in rainfed grown greengram (Vigna radiata) - K. Anandhi; G. Anand; S. Juliet Hepziba (Electronic Journal of Plant Breeding, 2019)
The low productivity is mainly due to fact that green gram is grown under rainfed environments with vagaries of monsoon. Hence stability of green gram genotypes was analysed during three years in rainfed condition in this study to identify stable genotypes. Among the 15 genotypes along with three checks studied the genotypes G14, G5 and G7 were stable genotypes with high mean yield. These three genotypes show stability for number of pods per plant. The genotype G14 also recorded the lowest value for days to 50 percent flowering with high stability showing early maturity.